Citrobacter koseri: A Cause of Silicone Oil Related Endophthalmitis after Post Pars Plana Vitrectomy - Luigi Sborgia; Valeria Albano; Giancarlo Sborgia; Francesco Boscia; Giovanni Alessio (Case Reports in Ophthalmological Medicine)
Purpose. We present a rare case of Citrobacter koseri culture-positive endophthalmitis in a postvitrectomy silicone oil-filled eye. Case report. A 64-year-old male patient presented to our ophthalmology emergency room with representative symptoms of acute endophthalmitis. He underwent a plana vitrectomy oil-filled tamponade previously. Preoperative and postoperative findings of the case were reported. Results. Culture tests of aqueous, silicone oil, and vitreous taps were positive for Citrobacter koseri. Conclusions. Culture-positive endophthalmitis in a silicone oil-filled eye has very rarely been in the literature. The described cases were caused by acute inflammatory reactions to silicone oil and were culture-negative. The postvitrectomy culture-positive endophthalmitis caused by Citrobacter is a very rare condition, and its management is not so smooth. Approaching with silicone oil removal, intraoperative intravitreal antibiotic injection, and silicone oil reinjection was performed in our case with good outcomes.